Waterborne diseases in flood compromised WASH conditions in Malaysia: a planetary health perspective - Jamalludin, Farah Humaira Binti; Ahmed, Minhaz Farid; Halder, Bijay; Khai, Tual Sawn; Asaduzzaman, Muhammad (Frontiers in Climate, 2025)
Floods are one of the major climate events that disrupt vital built systems such as water drainage and sanitation facilities. These conditions make it extremely difficult to obtain clean water and sanitation. The lack of safe and clean water, sanitation, and hygiene (WASH) has detrimental effects on the community, for example, the spread of a wide range of infectious illnesses, particularly waterborne illnesses. This review examines the major disease spread and difficulties encountered in a compromised WASH situation in Malaysia during flood catastrophes. We reviewed the literature on the Web of Science, SciELO Citation Index, PubMed, and Scopus databases for articles published between 1972 and 2024. Among the 41 identified articles, 10 were eligible for inclusion based on writing in English, removing duplicate literature, and observing that the study was conducted in Malaysia. This study discusses these issues and the WASH framework in Malaysia. Food poisoning, cholera, hepatitis A, diarrhea, and typhoid fever are among the most common ailments that flood victims are diagnosed with. Enhancing the WASH practices and infrastructure in Malaysia is crucial for reducing the risk of these illnesses. This requires a multifaceted strategy that includes sustainable technology, community involvement, and governmental action.